Image quality of abdominal ultrasonography after esophagogastroduodenoscopy is preserved by using carbon dioxide insufflation: A non-inferiority test in the same subject - Suda, Tsuyoshi; Shirota, Yukihiro; Takimoto, Hiroaki; Tsukada, Yasunori; Takishita, Kensaku; Nadamura, Takahiro; Miyazawa, Masaki; Hodo, Yuji; Wakabayashi, Tokio (PLOS ONE, 2022)
Because bowel gas deteriorates the image quality of abdominal ultrasonography (AUS), it is common to perform AUS prior to esophagogastroduodenoscopy (EGD). This one-way order limits the availability of examination appointments. To evaluate whether EGD using insufflation of carbon dioxide (CO 2 ), which is rapidly absorbed by the gastrointestinal mucosa, preserves the image quality of AUS performed subsequently, we designed a non-inferiority test in which each subject underwent AUS, EGD with CO 2 insufflation, and a second AUS, in that order. All saved AUS moving images were randomized and imaging quality was evaluated at 16 organs using a four-point Likert-like scale that divides the depiction rate by 25%. Sample size was calculated to be 26 using the following: non-inferiority margin of –0.40 corresponding to depiction rate of –10%, difference of means of 0.40, common standard deviation of 1.25, power of 90%, and 1-sided α-level of 0.025. We enrolled 30 subjects. The mean and 95% confidence interval (CI) of the image quality score of all 16 organs at pre- and post-EGD AUS in the 30 subjects were 3.54 [3.48–3.60] and 3.46 [3.39–3.52], respectively. The difference in the means was 0.08 of the scores, corresponding to a 2% depiction rate. The effect size was 0.172. The image quality of post-EGD AUS was not inferior, as demonstrated by the 97.5% CI of the difference, which did not cross the non-inferiority margin of –0.40. In conclusion, the use of CO 2 for insufflation in EGD does not cause much deterioration in the image quality of AUS performed subsequently. Therefore, it is permissible to perform EGD prior to AUS, which is expected to improve the efficiency of examination setup.